Народні назви шляхів сполучення Ровенщини - Антонюк, С. (Iнститут української мови НАН України, 2009)
Стаття присвячена аналізу народних назв на позначення шляхів сполучення Ровенщини, описаних за розміром, видом покриття, формою, якістю, функціональним призначенням, розміщенням стосовно інших географічних об’єктів. The article is devoted to the analysis of the folk names to denote the ways of communication in the Riwne Region. On the basis of the collected material the terms оf the investigated territory are described according to the size, kind of the cover, the form, the quality the functional purpose the placing according to other geographical objects.